PROBLEM-BASED LEARNING DI MI - Aziza, Rizda Shofa; Irfani, Dwi Rahayu; Saniyah, Nilna Minahus; Azzahra, Taqiya Fitria; Hikmah, Fitrotul Aini Mustika; Sahida, Dina Nur; Suttrisno, Suttrisno (STKIP Pesisir Selatan, 2025)
Problem Based Learning (PBL) is a learning approach oriented by students with realistic and complex problems that must be solved by students. PBL allows students to actively learn the learning process and improve critical thinking and problem solving. PBL can improve students' critical thinking, problem solving, and collaboration skills. The purpose of this study was to determine the effectiveness of the implementation of Problem Based Learning (PBL) in Madrasah Ibtidaiyah (mi) in improving students' critical thinking. The research method used was a class campaign study on student problems. The results of the study showed that the implementation of PBL can improve students' critical thinking skills. This is because students are more active and involved in the learning process. Students can also analyze problems, identify solutions, and present discussion results. Using PBL is a more comfortable learning experience that motivates students to learn.